Assessing Asset Indices - Filmer, Deon; Scott, Kinnon (World Bank, Washington, DC, 2012)
This paper compares how results using various methods to construct asset indices match results using per capita expenditures. The analysis shows that inferences about inequalities in education, health care use, fertility, child mortality, as well as labor market outcomes are quite robust to the specific economic status measure used. The measures-most significantly per capita expenditures versus the class of asset indices-do not, however, yield identical household rankings. Two factors stand out in predicting the degree of congruence in rankings between per capita expenditures and an asset index. First is the extent to which per capita expenditures can be explained by observed household and community characteristics. In settings with small transitory shocks to expenditure, or with little measurement error in expenditure, the rankings yielded by the alternative approaches are most similar. Second is the extent to which expenditures are dominated by individually consumed goods such as food. Asset indices are typically derived from indicators of goods which are effectively public at the household level, while expenditures are often dominated by food, an almost exclusively private good. In settings where private goods such as food are the main component of expenditures, asset indices and per capita consumption yield the least similar results, although adjusting for economies of scale in household expenditures reconciles the results somewhat.